Navigating complex authorities: Intellectual freedom, information literacy and truth in pandemic STEM information. (October 2022) - Mercer, Kate; Weaver, Kari D; Waked, Khrystine
Traversing scientific information has become increasingly fraught, as the new information landscape allows anyone to access endless information with a few keystrokes. However, those trying to find information, understand authorities and navigate experts need a deeper understanding not only of the information itself, but also of how and why information is shared. Increasingly, questions of expertise, locale and bias are driving the scientific information ecosystem and creating or expanding disinformation, misinformation and propaganda efforts. Librarians are in the centre of this maelstrom of information and are obligated to help people learn to be critical of information. This article presents an illustrative case study, using the example of scientific information around the safety and efficacy of the Oxford-AstraZeneca vaccine to demonstrate how modern scientific information sharing is shaped by the ways in which misinformation and fake news spread.